THE ORIGIN OF BEACH NAMES IN TANJUNGSARI: TOPONYMY STUDIES - Adab, Netiasa; Datang, Frans Asisi (UI Scholars Hub, 2021)
This toponymy study discusses the origin names of beaches in Tanjungsari Subdistrict, Gunungkidul Regency, Yogyakarta which are spread in three villages, namely Kemadang, Ngestirejo, and Banjarejo. This research aims to documents the naming of beaches in the area and classifies the naming into three presuppositions meaning based on Nyström’s theory, which are categorical, associative, and emotive meaning. This study used a qualitative research method. Research data were collected by means of observation and interviews with Village Hall officials and the community. The results of this study can be used to add information that can be conveyed to tourists. The results showed that categorical meaning on the beaches in Tanjungsari District is dominated by geographical condition, while the least is people’s name category. Associative presupposition meaning is dominated by neutral associative meaning, which are sea and conditions geographical. Meanwhile, the least dominant meaning of the associative presupposition is positive associative meaning. The dominant meaning of the emotive presupposition is the emotive meaning positive, which is happy. The least dominating out of the emotive presupposition meaning is the neutral emotive presupposition. Most beach naming comes from Javanese. This is influenced by the language spoken by most local community.